Organizational and legal problems of the program for the development of genetic technologies implementation - Natalya G. Zhavoronkova (Peoples’ Friendship University of Russia (RUDN University), 2021)
The relevance of this study is determined by the fact that at present legal regulation of genetic research is not comprehensive and does not provide a complete regulation of social relations in the focus. Оne of the factors hindering the development of genetic technologies is the absence of a basic law On genetic technologies. The purpose of the study . The article is devoted to the analysis of modern legal problems and the search for optimal solutions to the organizational and legal problems of the program for the development of genetic technologies implementation. Materials and methods of research . In order to understand modern approaches to relevant problems of improving the organizational and legal mechanism of the program for the development of genetic technologies implementation associated with environmental and biological risks and threats, a comparison of various methods of legal regulation and management, including dialectical, logical, and predictive methods, as well as the method of system analysis, is carried out. Results. Application of these methods allowed to conduct a comprehensive legal analysis of the current legislation and state strategic planning documents, work out a theoretical and legal basis for the development of the basic law On Genetic Technologies and formulate other proposals to improve the current legislation. The core powers of the National (federal) Bioresource Center, the network of federal and regional centers of genetic technologies, as well as the National Center for Biosafety have been identified and grounded by the authors.